The Extended Treatment Window's Impact on Emergency Systems of Care for Acute Stroke. (4th March 2019) - Miller, Joseph B.; Heitsch, Laura; Madsen, Tracy E.; Oostema, John; Reeves, Mat; Zammit, Christopher G.; Sabagha, Noor; Sozener, Cemal; Lewandowski, Christopher; Schrock, Jon W.
Abstract: The window for acute ischemic stroke treatment was previously limited to 4.5 hours for intravenous tissue plasminogen activator and to 6 hours for thrombectomy. Recent studies using advanced imaging selection expand this window for select patients up to 24 hours from last known well. These studies directly affect emergency stroke management, including prehospital triage and emergency department (ED) management of suspected stroke patients. This narrative review summarizes the data expanding the treatment window for ischemic stroke to 24 hours and discusses these implications on stroke systems of care. It analyzes the implications on prehospital protocols to identify and transfer large‐vessel occlusion stroke patients, on issues of distributive justice, and on ED management to provide advanced imaging and access to thrombectomy centers. The creation of high‐performing systems of care to manage acute ischemic stroke patients requires academic emergency physician leadership attentive to the rapidly changing science of stroke care.